Rehabilitation of a repatriated worker with spinal cord and brain injuries in a low-resource setting: A case report - Nobi, Md Golam (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: Combined spinal cord injury and traumatic brain injury pose complex rehabilitation challenges, particularly in low- and middle-income countries where structured neurorehabilitation services and transitional care pathways are limited. Repatriated migrant workers often return without ongoing rehabilitation, increasing reliance on family caregivers and risk of suboptimal functional recovery. Case description and management: We report a 27-year-old construction worker who sustained an incomplete L1 spinal cord injury (American Spinal Injury Association C) with mild traumatic brain injury following a fall abroad. After surgical stabilisation, he was repatriated to Bangladesh without rehabilitation and remained wheelchair dependent. On admission, he presented with paraplegia, spasticity, bowel and bladder incontinence, cognitive impairment, anxiety, and a sacral pressure ulcer. A physiatrist-led multidisciplinary team-based rehabilitation program was offered with intensive family caregiver training. His spouse was actively involved in daily care, learning pressure relief techniques, bladder management, transfer assistance, and emotional support strategies. Over ten weeks, the patient demonstrated significant improvements in motor strength, spasticity, cognitive orientation, bladder control, pain, and functional mobility, progressing to supervised ambulation. The spouse’s consistent involvement and skill acquisition were central to adherence and recovery. Conclusion: This case highlights that structured family caregiver training is a pivotal component of successful rehabilitation, enabling meaningful functional gains even in resource-constrained settings. Integrating caregivers into multidisciplinary care offers a practical, sustainable model aligned with WHO Rehabilitation 2030 priorities.